Pemilu Luar Negeri: Di Mana Suara, Aspirasi, dan Representasi Perempuan Pekerja Migran? - dwi yuni aresta, trisna; Anggraini, Titi Anggraini (Jurnal Perempuan, 2024)
The Overseas General Election deliberately neglects justice for Indonesian Female Migrant Workers (Perempuan Pekerja Migran Indonesia/PPMI). Structural layers of neglect occur from the formulation of regulations to their implementation. The economic contributions made by PPMI fail to be recognized by the state, as reflected in the fulfillment of their political rights during the general election. This article discusses the lost voices, aspirations, and political representation of PPMI due to poor Electoral District (Dapil) arrangements. The data in this article was gathered from 2024 monitoring activities conducted by Migrant CARE, an independent election monitoring organisation. The data was analyzed using Nancy Fraser’s political justice framework, which encompasses redistribution, recognition, and representation. The article identifies two interrelated issues: (1) problems in the arrangement of Electoral Districts for overseas elections that disrupt the connection between PPMI as constituents and both candidates and elected representatives; (2) the current Electoral District policies weaken state advocacy on issues faced by PPMI. This paper proposes and advocates for establishing a Special Overseas Electoral District to accommodate the voices, aspirations, and leadership of PPMI in politics in a meaningful way, thereby achieving representative political justice.